Analytical and Numerical Investigation to the Effect of Single Transverse Crack on the Dynamic Behavior of Rotor-Bearings System - Salam Ahmed, Abed; Jassim Farij, Thijel; Mohammad Reza, Bahrami (International Journal of Engineering and Technology, 2018)
This paper focused about the effect of single crack on the response and critical speed for rotor shaft which has a disc lies not at mid span supported by two journal bearings. First, found the dynamic behavior and parameters of journal bearings (stiffness and damping) and their Sommerfeld number with varies rotating speeds. The speed changing on eccentricity of journal with shaft center and on Sommerfeld number. Second, investigated the effect of changing of crack’s depth on the maximum response and critical speed for single cracked rotor. The comparison has been done between analytical and numerical results for uncrack and single cracked rotor by showing the discrepancy between them by using MATLAB & ANSYS for analytical and numerical methods respectively.
Keywords: rotor dynamics; cracked rotor; single crack; transverse crack; critical speed and dynamic behavior of the rotor-bearings system